THU0379 A 20 year single centre experience of aa amyloidosis demonstrating changes in its epidemiology. (23rd January 2014) - Lachmann, H.J.; Gillmore, J.D.; Wechalekar, A.D.; Gibbs, S.D.; Pinney, J.H.; Rowczenio, D.M.; Trojer, H.; Lane, T.; Venner, C.P.; Banypersad, S.M.; Gilbertson, J.A.; Hunt, F.T.; et al.
Abstract : Background: AA amyloidosis is the most serious potential complication of chronic inflammation and can result in renal failure and death. It is seen much less often in the USA than in Europe and is thought to have become less common in the developed world in general but there are few systematic data on its incidence and epidemiology. Objectives: To analyze a single national centre experience of AA amyloidosis in the United Kingdom over the past 20 years. Methods: Analysis of the UK National Amyloidosis Centres database and case records. Results: 493 patients with confirmed AA amyloidosis were assessed at the UK National Amyloidosis Centre between 1992 and 2011. The referral rate has been stable at ∼30 new cases/yr over the past 12 yrs, in contrast with a three-fold increase among other types of amyloidosis. Median age at referral was 55 years, 54% were male and 81% of cases were ethnically white. The commonest underlying diseases are: rheumatoid arthritis (RA) 28%, chronic sepsis 19% and seronegative arthritis 10%, but in 18% the underlying inflammatory disease was uncharacterized at diagnosis. Comparing the cohort referred 1992-96 with the most recent 5 years, there has been a reduction in patients with RA from 33% to 19% (p 0.038), and juvenile idiopathic arthritis from 18% to 2% (p<0.001), but a rise in AA amyloidosis of unknown aetiology from 8% to 28% (p<0.001). Age at referral has risen from a median of 48 to 61 years (p<0.001), and the proportion referred with established end-stage renal failure (ESRF) has remained stable at 26%. Median time to ESRF in cases presenting with an eGFR>20 ml/min is unchanged at 157 months. Median survival is 118 months with no significant difference between cohorts, but age at death has increased from a median of 60.6 yrs in the earliest cohort to 79 in the most recent (p<0.001). Conclusions: In contrast to a threefold increase in referrals of other types of amyloidosis during the past decade, referral rates for AA have not changed. Age at both diagnosis and death have increased significantly over the last 20 years. The incidence of AA amyloidosis among patients with inflammatory arthritis has decreased, perhaps reflecting greater use of biologic agents and a greater proportion of recent AA patients have uncharacterized underlying inflammatory disorders, posing challenges for clinical management. Disclosure of Interest: None Declared